2004
DOI: 10.1124/jpet.103.061713
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Drug Metabolism Enzymes and MDR1 Using a Novel Human Hepatocyte Cell Line

Abstract: Induction of drug-metabolizing enzymes and transporters can cause drug-drug interactions and loss of efficacy. In vitro induction studies traditionally use primary hepatocyte cultures and enzyme activity with selected marker compounds. We investigated the use of a novel human hepatocyte clone, the Fa2N-4 cell line, as an alternative reagent, which is readily available and provides a consistent, reproducible system. We used the Invader assay to monitor gene expression in these cells. This assay is a robust, yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(92 citation statements)
references
References 29 publications
5
87
0
Order By: Relevance
“…1A). Next, we asked whether shear stress increased the expression of an endogenous PXR target gene MDR1, which is a known PXR target encoding p-glycoprotein or ATP-binding cassette B1 (ABCB1), a transporter responsible for drug efflux (12,13). Quantitative reverse-transcriptase PCR (qRT-PCR) showed that MDR1 expression was induced by LSS, but not OSS, in human umbilical vein ECs (HUVECs) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A). Next, we asked whether shear stress increased the expression of an endogenous PXR target gene MDR1, which is a known PXR target encoding p-glycoprotein or ATP-binding cassette B1 (ABCB1), a transporter responsible for drug efflux (12,13). Quantitative reverse-transcriptase PCR (qRT-PCR) showed that MDR1 expression was induced by LSS, but not OSS, in human umbilical vein ECs (HUVECs) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The CYP3A1/2 enzyme activities were evaluated by the testosterone substrate assay [21] . The separation and detection of testosterone and its metabolites were performed using a Bisep™-1100 HPLC system (Unimicro Technologies Inc, USA), according to a previously described method [22] .…”
Section: Cyp3a1/2 Enzyme Activitymentioning
confidence: 99%
“…However, the sensitivity of hepatotoxicity using primary human hepatocytes or the HepG2 cell line cannot predict effects in early development and toxicological differences, which depend on the state of differentiation in hepatocytes (Knasmuller et al, 2004;Xu et al, 2004). In addition to, primary cells such as hepatocytes in particular and many transformed human hepatocyte-derived cell lines (immortalized cultures, i.e Fa2-N4 cells, HepaRG cells) have limitations in their life span and can have donor-dependent variations (Mills et al, 2004). However, they have disadvantages such as discontinuous phenotypic characteristics, functional properties and genetic instability.…”
Section: Limitation Of Traditional Toxicity Screeningmentioning
confidence: 99%